Sales promotion by wholesalers affects general practitioners' prescription behaviours in Japan. Issue 1 (1st January 2018) - Shimura, Hirohisa
ABSTRACT: Background : One method for promoting drugs in Japan has been utilizing wholesalers for promotion; however, the effectiveness of the sales promotion has been brought into question. Methods : A total of 74, 552 responses were collected from an internet survey of 511 prescribing doctors in hospitals with less than 19 beds, which recalled the visits by wholesalers' sales representatives (MS) in 2014. Each assessed the degree to which MS and/or sales representatives from a pharmaceutical company (MR) influenced a decision to prescribe each drug. The responses were analysed using the chi-square test and Goodman-Kruskal's gamma to evaluate the association between MS calls and doctors' prescription orders. Results : Results showed a significant effect of the MS calls on doctors' behaviours in terms of new drug prescriptions and subsequent behaviours. The results by therapeutic category showed a similar strong influence of the joint calls on new prescriptions on some therapeutic classes. The MS calls significantly influenced doctors to maintain and increase the prescription volume (p < 0.01). Conclusion : This paper demonstrates that sales promotion on the part of MSs and MRs adds value to the prescription decisions. Moreover, results suggest that MSs enhance prescription outcomes in competitive therapeutic categories.